Consensus techniques - Steve Jankowski (Internet Policy Review, 2024)
A core activity of decentralising internet projects has been participation, and with it the democratising potential of governing through consensus. This encounter between democratic ideals on one side and its integration into socio-technical projects on the other has had significant consequences for the purposes and meanings attached to consensus as a technique. While the democratic potential of developing such techniques is hopeful, there is a deep ontological question about consensus that has been rarely answered: to what degree is the meaning of consensus dedicated to decision-making and when is it committed to understanding? Additionally, to what degree do these techniques shape and set up the conditions for how we understand and encounter the meaning of consensus? The glossary entry examines these questions by tracing historical differences in general agreement to its diverse interpretations in liberal, feminist, and technocratic perspectives through the lens of cultural techniques and affordances, a combined approach that extends deliberative democratic theory by emphasising how the political is an effect of the tools enlisted to materialise it. The entry provides an overview of the consequences of these effects by delving into the Internet Engineering Task Force (IETF) and blockchain technologies where rough consensus, running code, and distributed consensus have been championed. However, this shift carries with it a significant drawback: the unintended technocratic co-optation of consensus for efficient decision-making, a trend that neglects the democratic necessity for fostering understanding amid disagreement. Aimed at both political theorists and internet researchers dedicated to the democratic potential of decentralising technologies, this entry serves as a feminist and media-sensitive guide to make democracy durable by emphasising the role consensus plays in creating understanding rather than decision-making.
Keywords: 300; Consensus; Sociotechnical decision-making; Democratic theory